STAGE-DEPENDENT RESPONSES OF VASCULAR AND PARENCHYMAL CELLS IN THE HYPERTENSIVE RAT BRAIN. (June 2022) - Ulbrich, Philipp; Morton, Lorena; Briese, Michael; Lämmlin, Naomi; Mattern, Hendrik; Hasanuzzaman, Mohammed; Westhues, Melina; Garz, Cornelia; Becker, Axel; Dityatev, Alexander; Jandke, Solveig; Yilmazer-Hanke, Deniz; et al.
Abstract : Objective: Long-term hypertension doubles all-cause dementia risk in aging by structural and functional alterations of the cerebral microvasculature and its surrounding tissue. However, therapeutical blood pressure lowering by itself is limited in its effectiveness depending on the progression of structural vessel remodeling, microvascular dysfunction and parenchymal tissue damage. Design and method: Therefore, the aim of this study was to investigate pathophysiological processes in different stages of hypertension. We explored acute, early- and late-chronic hypertension effects in the frontal brain of hypertensive rats, applying behavioral tests, histology, immunofluorescence, FACS and vascular/neural tissue RNA sequencing. Results: In response to initial increasing blood pressure and in absence of vascular pathology, microglia cells were found in close proximity to blood vessels and with morphological features of activation. Early chronic hypertensive animals showed frontal brain specific behavioral deficits, blood-brain-barrier leakage, leukocyte immigration, loss of glial reactivity and altered pathways related to cellular energy supply, protein synthesis and catabolism. In late chronic hypertension behavioral deficits and glial reactivity loss persisted. We also observed active angiogenesis, vascular fibroblast-related collagen aggregation and pathways related to decreased responsiveness to nutrients and increased metabolic demand. Additionally, we identified late-chronic vascular accumulation of insulin-like growth factor 1 (IGF1) binding proteins in brains of rats and humans with hypertensive cerebral small vessel disease, possibly attenuating protective IGF1 signaling in the cerebral microvasculature. Conclusions: Our results point towards stage-dependent reactions of vascular, glial, immune and neuronal cells in response to hypertension. Future studies have to verify, whether these mechanisms are valid in humans as well and whether they might be targeted to attenuate small vessel disease progression.